BEEPS At-A-Glance 2008 Cross Country Report - World Bank Group (Washington, DC, 2014)
The Business Environment and Enterprise Performance Survey (BEEPS), a joint initiative of the European Bank for Reconstruction and Development and the World Bank, now in its 4th iteration, is a means for collecting firm-level data on broad range of issues about the business environment and performance of firms, including business-government relations, firm financing, labor, infrastructure, informal payments and corruption, and other topics such as training and innovation. The BEEPS at-a-Glance cross country report provides an at-a-glance view of all country and sub-regional values for selected indicators. Similar to the country profiles, the report highlights changes in indicator values over time. In addition, this report provides an expanded analysis of Problems Doing Business indicators, including ranks over time and differences across time. As the report shows, there is much variation across countries and sub-regions for specific indicators, and in some cases, certain countries stand out as leaders and laggards. The BEEPS has been carried out in four rounds: in 1999, 2002, 2005, and 2008 and covers virtually all of the countries of Central and Eastern Europe and the former Soviet Union, as well as Turkey. This note focuses exclusively on the Main BEEPS questionnaires for 2005 and 2008 and presents simple averages over all firms with non-missing data. Many apparent changes over time may not be statistically significant. The Annex provides descriptions and definitions of the regional and sub-regional comparators.